Biomedical Hydrogels Fabricated Using Diels–Alder Crosslinking. Issue 3 (26th October 2020) - Cadamuro, Francesca; Russo, Laura; Nicotra, Francesco
Abstract : The Diels–Alder (DA) cycloaddition is one of the best methods for biomaterials conjugation to generate tools for biomedical applications. It is a biocompatible one‐step reaction, exploiting functional groups absent in natural biopolymers, doesn't require catalysts, and doesn't generate side products, an ideal "click reaction". In this review we provide an overview on the recent examples in which the DA cycloaddition has been exploited in nanomedicine. Nanoparticles for drug delivery or diagnosis, and nanostructured biomaterials for regenerative medicine, have been efficiently generated exploiting the DA reaction to crosslink the polymeric components, in order to obtain nanoparticles or scaffolds with the required chemical and morphological properties, and to conjugate targeting agents or signalling molecules. Abstract : The interest in Diels‐Alder conjugation for biomaterials development is constantly increasing. In this minireview we highlight how this one step reaction can be employed to develop drug delivery systems and scaffold for tissue engineering. An overview of recent examples is provided in which DA cycloaddition has been exploited under mild condition and eventually in presence of cells.